Global burden of stroke attributable to secondhand smoke in 204 countries and territories from 1990 to 2019: analysis of the global burden of disease study - Yang, Xinyue; Sun, Jiayi; Zhang, Wenjuan (Frontiers in Neurology, 2024)
Background Secondhand smoke (SHS) continues a significant public health concern globally. This study aimed to assess the global burden of stroke attributable to SHS exposure during 1990–2019. Methods This analysis utilized data on stroke morbidity and mortality from the Global Burden of Disease (GBD) 2019 study covering 204 countries and territories. We estimated stroke burden indicators attributable to SHS exposure, including age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life-year rate (ASDR), stratified by age, sex, region, and stroke subtype. Results In 2019, global SHS exposure accounted for 2.01 [95% uncertainty interval (UI): 1.49–2.58] million stroke mortality. The ASMR and ASDR were 2.5 (95% UI: 1.9–3.2) and 61.5 (95% UI: 46–78.8) per 100,000 population, respectively. The disease burden was higher among women than men and higher among the elderly than younger populations. Intracerebral hemorrhage and ischemic stroke had a more significant burden than subarachnoid hemorrhage. From 1990 to 2019, the ASMR and ASDR declined [estimated annual percentage change: −2.08 (95% CI: −2.21% to −1.95%) and −2.08% (95% CI: −2.19% to −1.97%) for each], but the absolute number of mortalities increased along with population growth. Substantial disparities existed across regions and sociodemographic groups. Conclusion Despite declining ASMR and ASDR over time, the absolute number of stroke deaths attributable to SHS continued to rise globally, imposing a considerable stroke burden worldwide. These findings can inform targeted interventions and policies aimed at SHS control.